Cancer Stem Cells in Tumor Modeling: Challenges and Future Directions. Issue 11 (5th November 2021) - Dogan, Elvan; Kisim, Asli; Bati-Ayaz, Gizem; Kubicek, Gregory J.; Pesen-Okvur, Devrim; Miri, Amir K.
Abstract : Cancer Stem Cells Microfluidic tumors‐on‐chips models have revolutionized anticancer therapeutic research by creating an ideal microenvironment for cancer cells. The current trend for modeling cancer stem cells in tumors‐on‐chips is discussed in article number 2100017 by Devrim Pesen‐Okvur, Amir K. Miri, and co‐workers. Opportunities for the incorporation of cancer stem cells with tumors‐on‐chips represent a paradigm shift in the cancer community by allowing clinicians to better predict which patients will benefit from chemotherapy treatments.